2016
DOI: 10.1177/0969733016680122
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in life of older persons: An integrative literature review

Abstract: Background: Meaning in life of older persons is related to well-being, health, quality of life, and “good life.” However, the topic is scarcely covered in nursing literature. Objective: The aim of this integrative review for nurses is to synthesize knowledge from scholarly literature to provide insight into how older persons find meaning in life, what are influencing circumstances, and what are their sources of meaning. The review serves as a starting point for including meaning in life of older persons as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 72 publications
7
56
0
1
Order By: Relevance
“…The recent literature indicates that the use of technology to help meditate, self-help, report mood and support mental health is beneficial for the internal growth of older adults (Finn, 2020). In addition, smart technology offers new opportunities for old people in distress when traditional resources are unreachable, unattainable or require special effort (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent literature indicates that the use of technology to help meditate, self-help, report mood and support mental health is beneficial for the internal growth of older adults (Finn, 2020). In addition, smart technology offers new opportunities for old people in distress when traditional resources are unreachable, unattainable or require special effort (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…personal computers, smart phones and tablets, software, Internet), on a daily basis, for communicating by e-mail, online video/phone calls, online chatting/instant messaging, using search engines, social networking sites, apps, word processing and online shopping (Finn, 2020). Moreover, higher levels of smart technology use seem to be significant predictors of reduced loneliness, higher levels of social support, fewer depressive symptoms, better self-rated health, fewer chronic illnesses, higher life satisfaction, purpose in life and well-being among older individuals (Finn, 2020). Additionally, artificial intelligence and algorithms have improved the diagnosis and treatment of older adults (Anderberg, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In research literature, human relationships are seen as the most important source of meaning in life. (27) Therefore, having and maintaining these social relationships and social communication is crucial for older persons. On this note, our study showed as well the lack of social contact and family support in frequent flyers.…”
Section: The Interaction Between Perceived Causes Contributing Factomentioning
confidence: 99%
“…In addition, human relationships have been reported to be the major source of meaning in the lives of elderly individuals . Social activity and relationships have been reported to be beneficial in various aspects of health and wellbeing, such as longevity, maintenance of activities of daily living, mental health, and cognitive function .…”
Section: Introductionmentioning
confidence: 99%